Karakteristik Pembelajaran Di Madrasah Analisis Keputusan Menteri Agama No. 347 Tahun 2022 Tentang Pedoman Implementasi Kurikulum Merdeka Pada Madrasah - Arif Shaifudin; Devi Ernantika (MA'ALIM: Jurnal Pendidikan Islam, 2026)
Madrasah is an Islamic educational institution under the auspices of the Ministry of Religion. When compared to educational institutions under the auspices of the Ministry of Education and Culture, madrasah has the advantage of integrating general knowledge with religion. Religious knowledge is an advantage for madrasahs to equip their alumni as a specialty in community life. The Kurikulum Merdeka is present as a macro policy that is currently being implemented in Indonesia which also has an impact on madrasahs. Independent learning which is the tagline of the Kurikulum Merdeka provides a fairly dynamic space for madrasahs to design school-level curriculum and learning so that it feels contextual to the needs of students and society. The article talks about KMA No. 347 of 2022 concerning Guidelines for the implementation of the Kurikulum Merdeka in Madrasahs, so that it is hoped that the characteristics of madrasahs will be seen in the context of the Kurikulum Merdeka.